A COMPARATIVE STUDY OF CLINICOHISTOPATHOLOGICAL CORRELATION IN PATIENTS OF PSORIASIS AND PSORIASIFORM LESIONS WITH KI67 AND CD34 IMMUNOHISTOCHEMICAL EXPRESSION - KALYANI VEMAVARAPU; SAMA SNEHAJA REDDY; SABBINENI RAMYA; BIJJAM RAJASHEKAR REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Psoriasis, characterized by chronic inflammation of the skin, stands as a notable example of a psoriasiform tissue pattern. In dermatology, the term “psoriasiform dermatitis” frequently appears across various inflammatory skin conditions, presenting challenges for dermatologists and pathologists alike in accurate differentiation. Relying solely on clinical features may prove insufficient in distinguishing between psoriasis and other psoriasiform dermatoses. Therefore, comprehensive differentiation requires consideration of clinical, histopathological, and immunohistochemical factors. Our study is to compare the clinicohistopathological features of psoriasis and psoriasiform dermatitis and to evaluate the immunohistochemical expression of CD34 and Ki67 in psoriasis and psoriasiform dermatitis. Methods: This retrospective study was conducted at the Department of Pathology, Mediciti Institute of Medical Sciences, Ghanpur, focusing on cases between January 1, 2020, and December 31, 2022. Clinical histories were extracted from requisition forms submitted by the Department of Dermatology. The study analyzed paraffin blocks from 50 patients each diagnosed with psoriasis and psoriasiform dermatitis. Formalin-fixed paraffin-embedded tissue samples were processed into 4-micron sections and initially stained with hematoxylin and eosin. The immunohistochemical analysis included primary antibodies against Ki-67 and CD34, with positive controls sourced from strongly positive samples of squamous cell carcinoma and capillary hemangioma, respectively. Appropriate negative controls were employed to ensure the accuracy of our findings. Results: In our study, we analyzed a total of 100 cases, comprising 50 cases each of psoriasis and psoriasiform dermatitis. Among the psoriasis cases, there was a male predominance with 29 males and 21 females, while psoriasiform dermatitis also showed male predominance with 32 males. The mean age was 33.8 years for psoriasis and 34.8 years for psoriasiform dermatitis. The majority of psoriasis cases fell in the 21–30 years age range, whereas for psoriasiform dermatitis, it was between 31 and 40 years. Significantly, our immunohistochemical analysis revealed that the mean staining intensity of the two markers was notably higher in psoriasis compared to psoriasiform dermatitis. Conclusions: In our study, we observed that the expression levels of Ki-67 and CD34 biomarkers were significantly elevated in psoriasis compared to psoriasiform dermatitis. Notably, four cases of psoriasiform dermatitis demonstrated positivity for CD34 in our analysis. This finding suggests a potential avenue for further research to explore the implications of CD34 positivity in psoriasis.